Preparation of Rutin Phytosome Complex - Khanh, Nguyen Van; Phuong, Doan Thi; Huyen, Nguyen Thi; Hai, Nguyen Thanh; Thanh Hang, Vu Thi (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 34 No 2DO - 10.25073/2588-1132/vnumps.4123, 2018)
Abstract: Rutin, a flavonol glycoside, has been reported to have antioxidant, anti-inflammatory, antithrombotic, antineoplastic effect, and can inhibit ultraviolet radiation-induced cutaneous oxidative stress and inflammation. The oral bioavailability of Rutin is very low. Phyto-phospholipid complex (phytosomes) is helpful in enhancing oral bioavailability and transdermal permeation of Rutin. Rutin phytosomes were prepared with phosphatidylcholine (PC) and cholesterol by solvent evaporation and spray drying method. The physicochemical properties of phytosomes were evaluated using particle size analyses, polydispersity index, Zeta potential, encapsulation efficiency, furrier transformation infrared spectroscopy (FTIR), differential scanning calorimetry (DSC) and X-ray diffraction (XRD). Phytosomes with the Rutin: PC: cholesterol molar ratios of 1:1:0.2, prepared by spray drying method showed the lowest particle size (266.4 nm) and the highest encapsulation efficiency (95.61%). The results of the FT-IR, DSC and XRD studies confirmed the phyto-phospholipid complex formation. Keywords: Rutin, Phytosomes, spray drying. References: Medina OP, Zhu Y, Kairemo K. Nanoparticles in cancer. Current Pharm Des,10 (2004) 2981. [2] Patel Amit, Tanwar Y.S, Suman Rakesh, Patel poojan. Phytosome: Phytolipid Drug Dilivery System for Improving Bioavailability of Herbal Drug. Journal of Pharmaceutical Science and Bioscientific Research, 3(2) (2013) 51. [3] Wonhwa L, Sae-Kwang K, Jong-Sup B. Barrier protective effects of rutin in LPS-induced inflammation in vitro and in vivo. Food and Chemical Toxicology, 50 (2012) 3048. [4] Pedriali CA, Fernandes AU, Bernusso LC, Polakiewicz B. The synthesis of a water-soluble derivative of rutin as an antiradical agent. Quím. Nova, 31(8) (2008) 2147. [5] Malay K Das, Bhupen Kalita. Design and Evaluation of Phyto-Phospholipid Complexes (Phytosomes) of Rutin for Transdermal Application. Journal of Applied Pharmaceutical Science, 4(10) (2014) 51. [6] Afshin Babazadeh, Babak Ghanbarzadeh, Hamed Hamishehkar. Phosphatidylcholine-rutin complex as a potential nanocarrier for foodapplications. Journal of Functional Foods 33 (2017) 134.